"The great chain of being sure about things": blockchain, truth, and a trustless network. Issue 1 (2nd January 2023) - Hartelius, E. Johanna
ABSTRACT: Often associated with the volatile cryptocurrency Bitcoin, a blockchain is a distributed ledger, an additive record of digitally networked transactions. On the assumption that technologies are cultural practices as much as they are instrumental, this essay contributes to the special issue on big data in communication by examining texts that constitute blockchain in a shared political imaginary and, in so doing, participate in blockchain's future. The essay analyzes how materials produced by IBM orient blockchain within contemporary ideals such as transparent access, immutability, and a single source of truth. Drawing on Sean Phelan's study of neoliberal politics and global media, including the naturalization of ideological values, the essay proposes that public discourses about blockchain evidence fundamental human desires to access truth and establish an infrastructure immune to corruption. The study finds that blockchain's decentralized infrastructure comports with a historical moment in which sociality itself is under intense pressure, and wherein the idea and practice of interconnected yet distrustful nodes make sense in the absence of functional governance. The essay concludes that in the routinized social practices of the blockchain's executive protocols, political potential is undercut by the absence of prospective and fundamental change.